Effects of the flood pulse on the isotopic composition (δ13C and δ15N) of the particulate organic carbon (POC) in the upper Paraná floodplain - Fiori, Leandro Fabrício; Sacramento, Patricia Almeida; Corbetta, Daiany de Fátima; Pereira, Lucas Milani; Benedito, Evanilde (Acta Scientiarum. Biological Sciences, 2014)
The particulate organic carbon (POC) is an important energy source present in the food chain of detritivorous fish. Considering its importance, this study aimed to investigate the effect of the flood pulse on the composition of the POC in a neotropical floodplain. For this, we analyzed the seasonal variations of the carbon isotopic composition (δ13C) and nitrogen (δ15N) in two different hydrological periods in the years 2000 and 2009. Sampling of potential sources of primary producers, as well as the POC, was held in different subsystems of the floodplain of the upper Paraná river (subsystems of the rivers Parana, Baía and Ivinheima). In 2000, there were significant differences on isotopic signature (δ13C) of the POC, unlike what was seen in 2009, where the values of δ13C were depleted us three subsystems, and showed significant differences both in the Paraná and Baia rivers. As this isotopic variation was attributed to the presence of flooding in 2009, that may be incorporated into new sources of the ecosystem. This is contrary to what was observed in 2000, when they were filled with recorded values below3.5 m fluviometric. Thus, it can be concluded that the flood event has an effect on the composition of POC and therefore can directly influence the structure of fish food chains scavengers of the basin.